High-activity placenta-derived mesenchymal stem cells combined with low-intensity extracorporeal shock wave therapy for diabetic erectile dysfunction: a prospective randomized controlled trial - Yun-Hua Ji; Yi-Fan Zhang; Xiao Tan; Hao-Zhong Hou; Zhen Yao; Bo Zhang (Stem Cell Research & Therapy)
Abstract Objective To evaluate the efficacy and safety of high-activity placenta-derived mesenchymal stem cells (hPMSCs) in combination with low-intensity extracorporeal shock wave therapy (LI-ESWT) for the treatment of diabetic erectile dysfunction (ED). Methods This prospective, randomized, controlled clinical trial enrolled 33 patients with refractory diabetic ED. Participants were randomly assigned in a 1:1:1 ratio to one of three groups: the hPMSCs group, the LI-ESWT group, or the combined therapy group (H + L). All subjects discontinued ED medications for at least two weeks prior to receiving the intervention. Treatment efficacy was assessed at baseline and at 1,3 and 6 months post-intervention using the International Index of Erectile Function – Erectile Function (IIEF-EF), Erection Hardness Score (EHS), Sexual Encounter Profile (SEP-2/SEP-3), and Rigiscan parameters, with safety outcomes monitored concurrently. Results At the 6-month follow-up, the combined therapy group demonstrated significantly superior outcomes compared to the individual hPMSCs and LI-ESWT groups. Specifically, total erection time reached 22.20 (15.20, 30.25) minutes (p = 0.001) and full erection time reached 11.90 (11.55, 12.35) minutes (p = 0.004) in the combined group. Moreover, EHS scores improved markedly, with 70% of patients in the combined group achieving an EHS > 2 at 6 months (p = 0.045). No severe adverse events were observed in any group; any local mild pain resolved within one week. Conclusion The combination of high-activity hPMSCs and LI-ESWT appears to be a safe and effective strategy for improving erectile function in patients with diabetic ED, demonstrating a synergistic effect in prolonging erection duration and enhancing penile hardness. This combined therapeutic approach represents a promising new option for the clinical management of diabetic ED, warranting further validation in larger, multi-center studies to confirm its long-term efficacy and safety.